OCCURRENCE OF TAENIA HYDATIGENA IN WILD CARNIVORES ACROSS DIFFERENT FOREST RANGES IN THE NILGIRIS, TAMIL NADU, INDIA - S.T. Bino Sundar; K. Rajesh Kumar; M. Aravind; K. Jeeva; S. Shiyamala; B. Nishanth; P.N. Richard Jagatheesan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The paper presents the findings on occurrence of cestode infection in wild carnivores during postmortem examination across different forest ranges in the Nilgiris district of Tamil Nadu, India over a period of sixteen months. A total of 37 wild carnivores comprising of seven dholes, four leopard cats, ten tigers and 16 leopards were examined from December 2023 to March 2025. Postmortem examination was conducted by the forest veterinary officer following standard procedures. The tapeworms were collected, labelled, processed as per standard procedures, identified and photographed. Out of the 37wild carnivores, 11 were found infected with cestodes (29.72%) which were identified as Taenia hydatigena morphologically. This comprised of one leopard cat (25%), two dholes (28.57%), five tigers(50%) and three leopards (18.75%). Out of the 11 infected animals, six were males (54.54%) and five were females (45.45%). Also, among the infected animals, one was below one year of age (9.09%) and 10 were above one year of age (90.90%).